Utilization of incineration bottom ash, waste marine clay, and ground granulated blast-furnace slag as a construction material - Sun, Xinlei (2022)
The growing population and rapid urbanization have accelerated the global generation of solid waste and increased the demand for construction materials. In this context, the utilization of solid wastes as construction materials can not only eliminate the landfilling of solid wastes, but also alleviate the demand for construction materials and reduce the burden of consuming natural aggregates. Hence, this study investigated the utilization of two solid wastes, fine incineration bottom ash (IBA) and waste marine clay (MC) as a construction material. A industry by-product, ground granulated blast-furnace slag (GGBS), was used to further increase the strength and reduce the leaching of heavy metals of IBA-MC; the traditional binder, ordinary Portland cement (OPC), was also used as comparison. The results showed that IBA and MC can complement each other's limitations, i.e. IBA largely reduced the water content of MC; MC reduced the leaching concentrations of heavy metals from IBA. The addition of GGBS and OPC significantly increased the strength of IBA-MC. For instance, the UCS of GGBS-IBA-MC with IBA/MC ratio of 7/3 and GGBS content of 7.5% (2805 kPa) was more than 10 times higher than that of IBA-MC (247 kPa). With the addition of GGBS, the leaching of heavy metals of GGBS-IBA-MC further decreased compared with IBA-MC and OPC-IBA-MC. For GGBS contents of 5% and 7.5%, leaching concentrations of all studied heavy metals in GGBS-IBA-MC with IBA/MC ratios of 5/5 and 7/3 satisfied the requirements of DNK-Category 3 for construction materials. The X-ray diffraction (XRD) and Scanning Electron Microscope with energy dispersive X-ray spectrometry (SEM-EDX) tests were also carried out and the hydration products such as ettringite and calcium silicate hydrate (CSH) were identified as the main reasons for improved strength. To sum up, GGBS-IBA-MC has the potential to be used as a construction material.